The effects of two maximum grip strength training methods using the same effort duration and different edge depth on grip endurance in elite climbers - López-Rivera, E.; González-Badillo, J. J. (Sports Technology, 2012)
Nine experienced rock climbers (mean climbing ability of 8a+/b) were randomly assigned to Group A (n = 5) and Group B (n = 4). Both groups trained dead hanging using two different methods. One method consisted of using the minimum edge depth (MED) they could hold the weight of their body; the other consisted of using a bigger edge (18 mm) with maximum added weight (MAW). Group A performed MED from Weeks 1 to 4, and then performed MAW the following 4 weeks (termed as MED-MAW group); Group B performed MAW from Weeks 1 to 4 and then performed MED the following 4 weeks (termed as MAW-MED group). Maximum grip strength and endurance tests were conducted initially (ST1; ET1), following 4 weeks (ST2; ET2), 8 weeks (ST3; ET3), 2 weeks (ST4; ET4) and 4 weeks (ST5; ET5) completion of training to determine the effects of detraining. The 9.6% improvement in grip strength (p>0.05) in MAW-MED group in ST2 and 6.9% in ST4 was greater than in MED-MAW group. In terms of grip endurance, MAW-MED group in ET2 (16.69%) and in ET3 (19.95%) improved more than MED-MAW group (p>0.05). Significant positive correlation was found between ST and ET, and between changes in strength and changes in endurance at all stages, controlling for body weight in all cases. The present data suggest that the most effective sequence of finger strength training methods is MAW-MED.